Utilização de um aplicativo de simulação computacional na avaliação de desempenho térmico de protótipo de habitação de interesse social (his) - Oliveira, Rodrigo Porto (2010)
This Masters Degree dissertation seeks to make a comparative study of internal air temperature data, simulated through the thermal computer application DesignBuilder 1.2, and data registered in loco through HOBO® Temp Data Logger, in a Social Housing Prototype (HIS), located at the Central Campus of the Federal University of Rio Grande do Norte UFRN. The prototype was designed and built seeking strategies of thermal comfort recommended for the local climate where the study was carried out, and built with panels of cellular concrete by Construtora DoisA, a collaborator of research project REPESC Rede de Pesquisa em Eficiência Energética de Sistemas Construtivos (Research Network on Energy Efficiency of Construction Systems), an integral part of Habitare program. The methodology employed carefully examined the problem, reviewed the bibliography, analyzing the major aspects related to computer simulations for thermal performance of buildings, such as climate characterization of the region under study and users thermal comfort demands. The DesignBuilder 1.2 computer application was used as a simulation tool, and theoretical alterations were carried out in the prototype, then they were compared with the parameters of thermal comfort adopted, based on the area s current technical literature. Analyses of the comparative studies were performed through graphical outputs for a better understanding of air temperature amplitudes and thermal comfort conditions. The data used for the characterization of external air temperature were obtained from the Test Reference Year (TRY), defined for the study area (Natal-RN). Thus the author also performed comparative studies for TRY data registered in the years 2006, 2007 and 2008, at weather station Davis Precision Station, located at the Instituto Nacional de Pesquisas Espaciais INPE-CRN (National Institute of Space Research), in a neighboring area of UFRN s Central Campus. The conclusions observed from the comparative studies performed among computer simulations, and the local records obtained from the studied prototype, point out that the simulations performed in naturally ventilated buildings is quite a complex task, due to the applications limitations, mainly owed to the complexity of air flow phenomena, the influence of comfort conditions in the surrounding areas and climate records. Lastly, regarding the use of the application DesignBuilder 1.2 in the present study, one may conclude that it is a good tool for computer simulations. However, it needs some adjustments to improve reliability in its use. There is a need for continued research, considering the dedication of users to the prototype, as well as the thermal charges of the equipment, in order to check sensitivity